Fracture strength of endodontically treated teeth restored with novel CAD/CAM ceramic post systems - Omur Dede, Dogu; Celik, Ersan; Tulga, Ayca; Sariyilmaz, Evren; Cakici, Fatih; Bahar Cakici, Elif; Kahveci, Cigdem (Annals of Medical Research, 2021)
Aim: The purpose of this study was to investigate the fracture strength (FS) and fracture types of endodontically treated teeth that restored with CAD/CAM made novel ceramic posts.Materials and Methods: Seventy human maxillary central incisors were selected, endodontically treated and expanded to 1.8 mm diameter with leaving of 2-3 mm canal filling. The teeth were randomly divided into 7 post restoration groups (n=10); a glass fiber post system as control (GFbr), monolithic zirconia (GMzr), lithium disilicate (GLds), zirconia-reinforced lithium silicate (GZr_Lds) ceramics, nanoparticle-filled (GRmc_Cer), resin nano-ceramic (GRmc_Lu), and polymer-infiltrated (GRmc_En) resin matrix ceramic groups. Then composite cores were build-up, crown restorations fabricated, and incubated in a water bath (37 ± 10C, 24 hours). A dynamic load was applied at 135° to the long axis of each specimen with a crosshead speed of 1 mm/min. FS and fracture types (favorable-catastrophic) were recorded. The FS values were statistically analyzed with one-way ANOVA and Tukey HSD tests (α=.05). Results: While the FS values of GMzr (365.62 ± 28.52 N) was significantly higher than GFbr (261.07 ± 24.51 N), all other groups (167.09-191.64 N) significantly lower, according to the Tukey HSD (P.05). Catastrophic fractures were observed only for GMzr. Conclusion: The results of this study suggest that the novel CAD/CAM ceramic materials substantially be suitable for the rehabilitation of severely damaged teeth with composite resin core build-up in the anterior region. However, only the monolithic zirconia post restorations may be more durable than the glass fiber post systems.